THE PHENOMENOLOGY STUDY: POST-FLOOD AND LANDSLIDE FARMERS RESILIENCE EXPERIENCES IN VILLAGE - FITRIO DEVIANTONY (Jurnal Ilmiah Kesehatan Media Husada, 2020)
Floods and landslides are disasters that can cause a lot of damage related to the material and of course fatalities, as well as the amount of damage from the environment that occurs, and other impacts will undoubtedly affect the psychology of the communities that changed by the disaster. The psychological effect of this unusual event will undoubtedly lead to trauma or it called posttraumatic stress disorder (PTSD). This study aims to explore the experiences of farmers who experience floods and landslides directly, the research design used is a qualitative research design using an interpretative phenomenology approach. The technique of collecting data used in-depth interviews with a semi-structured interview guide involving five participants and analyzed using interpretative analysis of phenomenology. This study produced six themes including disasters that occur due to humans, accepting the existing reality, getting closer to God, having the desire to farm again, recovering the family economy, keeping the environment around and improving themselves. The role of health workers is important because the impact caused by this condition can be worse so that health workers need to provide services so that farmers can understand, live and be able to accept and adapt to the conditions that occur